AUDIT QUALITY IN SOEs BASED ON THE INTERNAL CONTROL OF COMPANY ASPECT - Lita Natalia; R Nelly Nur Apandi; Agus Widarsono (Jurnal Riset Akuntansi dan Keuangan, 2024)
Public accounting, a profession held in high regard by the public, instills confidence in business owners by ensuring a thorough audit process and delivering expert opinions on their financial accounts. Emphasizing the significance of audits, it is crucial to note that the primary goal of auditors is to ascertain if financial statements are presented accurately and in compliance with the relevant financial accounting system, hence providing assurance to users of these accounts. Currently, the performance indicators of numerous state-owned firms remain inefficient. This study intends to examine the influence of internal control comprehension on audit quality in state-owned enterprises in Indonesia. The selected research approach is quantitative, employing a causal associative study design. This study will encompass all Indonesian State-Owned Enterprises in 2023, comprising 30 businesses with a financial reporting period of 2022. The data analysis technique employed will be Logistic Regression. The findings of this study indicate that the quality of audits is affected by the extent of comprehension of internal control through monitoring. The level of internal control involving the control environment, risk assessment, control activities, and information and communication has little impact on Audit Quality at BUMN in Indonesia.